ANALISIS PRODUKSI TEMPE BUNGKUS DAUN PISANG DI DESA LOA PARI KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA (The Production Analysis of Banana Leaves-Wrapped Tempe in Loa Pari Village Tenggarong Seberang Subregency Kutai Kartanegara Regency) - VODI FEBRIADI; SITI BALKIS (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2022)
The purposes of this research  were to know the production cost, revenue, and profit of tempe production, the influence of soybean usage to tempe production level, total product, average product, and marginal product of production of banana  leaves wrapped tempe . The research was conducted from April to June 2016 in the Village of Loa Pari, Subregency of Tenggarong Seberang, Regency of Kutai Kartanegara. Sampling used  census method and data were collected by direct observation and interview to 20 respondents. The data were analyzed to calculate total cost, revenue, income, total product, average product, and marginal product. The results of this research showed the average production cost of IDR4,728,311.40 month-1, the average revenue of IDR11,100,000.00 month-1, and the average income of IDR6,371,688.60 month-1. The use of soybeans will affect tempe production. Total production of banana leaves  wrapped tempe was 22,200 packs month-1. The average production of banana leaves wrapped tempe was 733 packs days-1. The marginal production of banana leaves wrapped tempe was 25 packs kg-1.